LEXICAL OCCASIONAL UNITS EXPRESSING THE MEANING OF SIGN AND ACTION - Mokhinur Kurbanova (Sciental Journals Publishing, 2025)
The article analyzes occasional units, their classification into certain types by linguists, occasional units expressing the meaning of a sign and action-state from a semantic-stylistic point of view through examples.
Keywords: lexical (lexical) occasionalisms, semantic (semantic) occasionalisms, phraseological occasionalisms (occasional expressions), artificial occasionalisms (occasional constructions), syntactic occasionalisms (occasional combinations), begonaparvar, dostanistan, jannatlashaylik, banglanglar, occasional meaning.